Trypanosoma cruzi Sirtuin 2 as a Relevant Druggable Target: New Inhibitors Developed by Computer-Aided Drug Design - Glaucio Monteiro Ferreira; Thales Kronenberger; Vinicius Gonçalves Maltarollo; Antti Poso; Fernando de Moura Gatti; Vitor Medeiros Almeida; Sandro Roberto Marana; Carla Duque Lopes; Daiane Yukie Tezuka; Sérgio de Albuquerque; Flavio da Silva Emery; Gustavo Henrique Goulart Trossini (MDPI AG, 2023)
Trypanosoma cruzi, the etiological agent of Chagas disease, relies on finely coordinated epigenetic regulation during the transition between hosts. Herein we targeted the silent information regulator 2 (Sir2) enzyme, a NAD+-dependent class III histone deacetylase, to interfere with the parasites' cell cycle. A combination of molecular modelling with on-target experimental validation was used to discover new inhibitors from commercially available compound libraries. We selected six inhibitors from the virtual screening, which were validated on the recombinant Sir2 enzyme. The most potent inhibitor (CDMS-01, IC50 = 40 μM) was chosen as a potential lead compound.